RESEARCH OF HYDROTHERMAL PROCESSING OF DRY BARLEY MALT - O. S. KOVALOVA; Yu. O. CHURSINOV; D. D. KOFAN (Zernovì Produkti ì Kombìkorma, 2018)
Functional properties of food products with the addition of germinated grain raw materials have become the object of increased attention of scientists and specialists in the food industry. In addition to the nutritional ingredients, food products with the addition of grain raw materials contain functional ingredients that positively affect the human body that helps to adapt to the effects of the external environment. Functional products with the addition of germinated grain are considered not only as a source of plastic substances and energy but also as a nutritional complex that provides a healing effect. The usage of germinated grain in the food and processing industries is very limited due to its short shelf life and the characteristics of preparing malt for further processing. A relevant technological challenge is the selection of barley malt moisture regimes. The cycle of researches concerning hydrothermal processing of dry barley malt has been carried out. The purpose of determining the optimal technological regimes of hydrothermal processing of dry germinated grain is the prospects for its further use in various food technologies as a food additive or a component of the enrichment of products with biologically active substances. The work highlights the selection process and the main technological parameters of the process that can be used in the industrial processing of barley malt. As a research object, dry germinated grain (malt) produced by a special technology was used. In the course of research, an optimal hydro module was selected for humidifying barley malt, the temperature regime of hydrothermal processing of germinated grain was determined, the degree of swelling of malted grain was determined, the optimum time of wetting of raw materials for its further processing was determined. When analyzing the data obtained, it was concluded that the optimal hydro module for swelling barley malt is 1:4, the optimum temperature is +65С and the duration of hydrothermal processing is 48 hours. The regimes of hydrothermal processing of barley malt presented in the article will allow optimizing the technological process of malt processing.